Floristic composition of four habitats in Las Papas de Arriba ranch, municipality of Ojuelos de Jalisco, Jalisco, Mexico - Harker, Mollie; Garcia Rubio, Luz Adriana; Riojas-López, Mónica E. (Instituto de Ecología, A.C., 2008)
Floristics and plant physionomy of four habitats were studied in the Papas de Arriba ranch, Ojuelos de Jalisco, Jalisco: xerophilous scrub, natural grassland, an established orchard of prickly pear (Opuntia spp.) and other recently planted fields of prickly pear. The list presented includes 356 species and subspecific entities, representing 73 families and 230 genera of vascular plants. The families with most genera and species are Asteraceae (48/76), Poaceae (29/46), Fabaceae (13/19) and Cactaceae (6/19), while the richest genera are Opuntia (10), Euphorbia (9), Solanum (7), Pseudognaphalium (6), Bouteloua (6), Ipomoea (6) and Muhlenbergia (6). Thirty six percent of the species are endemic to Mexico and only 4% are introduced. Included in the list are 9 species not reported before from Jalisco and 5 species of threatened plants. Herbs are the dominant guild including 108 annuals and 177 perennials, together 285 species (80% of the flora). The xerophilous scrub presents the greatest alpha diversity with 223 species (62.6% of the total), while there are 119 (33.4%) in the grassland, 138 (38.8%) in the established orchard and 132 (37.1%) in the recently planted fields. The xerophilous scrub also has the greatest number of exclusive species and is more complex with 7 plant life forms represented there. The Opuntia orchard and recently planted fields are most similar floristically sharing 35% of the species.